The Effectiveness of The Convention on the Rights of the Child (CRC) Regime by UNICEF in Encouraging the Implementation of Child Protection in SoutheastAsian Countries - Rizky, Lucitania; Salampessy, Muhammad Ade Safri; Achdyana, Isna (JASSP, 2022)
The Convention on the Rights of the Child is a regime that exists as a humanitarian effort in the context of realizing protection and becoming a real guarantee of children's rights in the world. This regime was conceived as a convention since the end of World War I, in which the war has left sadness and trauma for the global community. The Convention on the Rights of the Child emerged at the instigation of women activists and wanted to draw world attention to the plight of children who were victims of war. In its development, the CRC regime was later ratified as an international regime by the United Nations on November 20, 1989 and has coercive power on September 2, 1990. To this day, CRC has been ratified by 196 countries in the world, including all ASEAN member countries. In its implementation, ASEAN has become an international organization with a regional orientation in Southeast Asia that focuses on upholding children's rights. ASEAN established various blueprints to encourage countries in Southeast Asia to work together to protect children. So far, all ASEAN countries have implemented CRC in positive law and various strategic programs in their countries. This study aims to compare the effectiveness of a regime in encouraging real efforts of a country in implementing a regime. In line with the issue of protecting children's rights in Southeast Asia, this research is encouraged to examine the effectiveness of the implementation of the Convention on the Rights of the Child in Southeast Asia using Stokke's theory of regime effectiveness.